Pengaruh Abdominal Stretching Exercise Terhadap Penurunan Nyeri Haid Pada Remaja - 88, yuniza (Masker Medika, 2021)
Background: Menstrual pain is a common problem in women of reproductive age.menstrual pain begings a few hours before or at the time of menstrual bleeding and lasts for 2-3 days. The pain is most intense during the first 24-36 hours of menstruation.pharmacological and non-pharmacological therepy is a way that can be done to eliminate and reduce menstrual pain. One of the non-pharmacological metods is to do abdominal stretching exercise. Objective: To determine the effect of abdominal stretching exercise on reducing menstrual pain scale in adolescents. Methods: This research design uses quantitative research, namely pre-experimental that is usingthe type of one group prettest design. The population in this study were 222 ikrst mp students and 31 students who met the inclusion criteria. The measurement of the menstrual pain scale in this study used the Nuumeric Rating Scale (NRS). Results: There was an effect of Abdominal Streching Exercise on the reduction of menstrual pain in adolescents seen from the P value with a value of 0.000 which means that the value is <0.05. Conclusion: There is an affect of abdominal stretching exercise on the reduction of mentrusal pain in adolescents. Keywords: Abdominal Streching Exercise, Menstrual pain, Adolescents